Extension of a novel diagnostic index to include soft tissue injuries: Modified Eden Baysal Dental Trauma Index. Issue 6 (27th September 2021) - Eden, Ece; Onetto, Juan Eduardo; O'Connell, Anne C.
Abstract: Aim: Accurate records of traumatic dental injuries are important for clinical management and data collection for research. Soft tissue injuries often accompany dental trauma and should be appropriately recorded. The Eden Baysal Dental Trauma Index (EBDTI) provides an easy recording system of useful information about traumatic dental injuries on a tooth basis. The aim of this study was to extend the EBDTI index to record soft tissue injuries in a concise format and to approve the face and content validity of this version as the modified EBDTI (MEBDTI). Materials and Methods: An extension to EBDTI was developed by adding superscript numbers from 0 to 8 to represent soft tissue injuries related to dental trauma. The Rand e‐Delphi method was used to evaluate this version of the index. A definition and two statements about the index were sent to 15 international panel experts to be assessed independently on a 9‐point Likert scale where 1 represented "total disagreement, " and 9 indicated "total agreement." The panel needed to reach a 75% consensus for validation. A numerical code was suggested using zero to depict no soft tissue injury; 1–4 to record extra‐oral injuries; and 5–8 to record intra‐oral injuries (for example, gingiva, frenulum, and palate). Traumatic dental injury of the tooth/teeth is recorded using EBDTI in square brackets, and soft tissue codes are used as superscript numbers outside the brackets on a patient basis. Results: The panel reached a consensus on the definition (86.7%) and two statements (86.7% and 93.3%) in one round. Various cases are presented to demonstrate the application of the index. Conclusion: The Modified Eden Baysal Dental Trauma Index was developed to record soft tissue. injuries on a patient basis and was approved for face and content validity.